Feto-maternal outcome in primigravida with unengaged head vs engaged head at term - Yadav, Vaishali; Agarwal, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Labor, defined as regular uterine contractions followed by cervical dilation, effacement, and descent of the presenting part, is a pivotal event in a woman’s life. Fetal head engagement, where the widest diameter of the head crosses the pelvic brim, is crucial for a favorable vaginal delivery. This study focuses on primigravidae, where labor dynamics can differ significantly compared to multigravida, often resulting in prolonged labor and increased cesarean sections. Methods: The study involved primigravidae at term (37-42 weeks) presenting at the labor ward. Inclusion criteria were first-time mothers with singleton pregnancies and vertex presentations. Exclusion criteria included multiple pregnancies, breech presentations, and preterm labor. Results: Primigravidae with unengaged fetal heads had significantly longer labor durations (12.7±3.6 hours vs. 8.5±2.3 hours, p<0.01), higher cesarean section rates (45% vs. 20%, p<0.01), and increased maternal complications (30% vs. 10%, p<0.01). Neonatal outcomes were also poorer in the unengaged group, with higher rates of neonatal ICU admissions and lower Apgar scores. Conclusions: Primigravidae with unengaged fetal heads at term are at increased risk of prolonged labor, higher cesarean sections, and adverse maternal and neonatal outcomes. Effective management, including careful monitoring and timely interventions, is crucial to improving outcomes. Future research should focus on identifying predictors of engagement and developing guidelines for managing unengaged fetal heads in labor.